Increasing Opportunity and Value in the Cultural Industries: A Comparative Analysis of the Successful Clusters and Implications for Hallyu - Moon, Hwy-Chang (Archīum Ateneo, 2024)
Despite the growing digitalization and globalization, the industrial map of the world remains to display high-level concentration of resources and productivity in certain geographical locations called clusters. These locations such as Silicon Valley and Hollywood continue to attract entrepreneurs and large firms, enjoying strong sustainability and competitiveness. As the agglomerate of diverse entities and institutions, clusters play a significant role for improving the overall growth of the industry. This is more evident in the cultural industries where the relatively high unpredictability, expanding scale of investments, and the importance of physical location for consuming cultural contents require firms and participants to cooperate in proximity. In order to examine the importance of clusters in the cultural industries, this study first conducts a theoretical review on the role of clusters in this industry. Then, the paper analyzes the historically meaningful cultural clusters, Italy during the Renaissance and the US Hollywood of modern times, by evaluating the role of four interactive factors: firm, people, education, and government. The analysis of these two cases reveals that the interactions among the four factors significantly influence the scale and competitiveness of cultural clusters. Ultimately, the paper provides some important options for further development of the Korean wave or Hallyu by utilizing the cluster strategy.